The Rise and ambivalent development of Hármashatár Hill, a tourist destination in Budapest - Csemez, Attila (4D Journal of Landscape Architecture and Garden Art, 2024)
There have been significant differences in the tourism development amongst the various sections of the Buda Hills near Budapest. Reasons for the differences in development include the characteristics of the neighbourhoods adjacent to the forested hills, the development of urban transport networks, topography, tourist attractions and forest cover. In the forests stretching from Széchenyi Hill to Hűvösvölgy, hikers were already present at the end of the 19thcentury. As for the mountain range from Mátyás Hill to Csúcs Hill, the first steps of tourism development took place in the 1930s only. The Árpád Lookout Towerwas opened in 1929, the hiker’s lodge on Hármashatár Hillin 1932 and the pilot’s quarters and hangars of the gliding airfield in 1940. After the Second World War, the glider base north of the summit of Hármashatár Hill was take nunder the management of national defence, and a ’jamming station’ was built on the southern side. Visitors were already uncomfortable due to the closed military are asall around, and this was exacerbated by the relocation of marked tourist routes leading to the summit. The forest of antennas at the summit of Hármashatár Hill was not attractive to tourists either. The rocky grass lands, whichare sensitive to trampling, have been severely damaged by the crowds arriving by bus ’H’ by picking flowers, picnicking and winter tobog ganing. With the constructionof the training ground of the Hungarian Defence Asso-ciation (MHSZ) in 1973, the vegetation on the western slopes of Hármashatár Hill was permanently damaged. The vegetation was destroyed by hang gliders and then by paragliders at the launch sites. Thanks to Pilisi Parkerdő Plc., the touristically poor conditions on Hármashatár Hill have been continuously improved: Guckler Károly Look-out Tower was opened in 2016, a hiker’s lodge was openedon the formerly closed area, and a buffet was opened to welcome visitors. However, the view of the antennas, the MHSZ training ground and the remains of the fences are still to be removed from around the 495m summit.